Best-Link Matching of Scottish Health Data Sets - Kendrick, S. W.; Douglas, M. M.; Gardner, D.; Hucker, D. (Methods of Information in Medicine, 1998)
Methods are described used to link the Community Health Index and the National Health Service Central Register (NHSCR) in Scotland to provide a basis for a national patient index. The linkage used a combination of deterministic and probability matching techniques. A best-link principle was used by which each Community Health Index record was allowed to link only to the NHSCR record with which it achieved the highest match weight. This strategy, applied in the context of two files which each covered virtually the entire population of Scotland, increased the accuracy of linkage approximately a thousand-fold compared with the likely results of a less structured probability matching approach. By this means, 98.8% of linkable records were linked automatically with a sufficient degree of confidence for administrative purposes.
Keywords: Medical Record Linkage; Community Health Planning; Probability Theory; Registries